Wonderful world [videorecording (DVD)] - Goldin, Josh; Broderick, Matthew, 1962-; Lathan, Sanaa; Williams, Michael Kenneth; Ferguson, Jesse Tyler; Walker, Ally, 1961- (Magnolia Home Entertainment, 2010)
Ben Singer is a failed folk singer, newly unemployed proofreader, and every-other-weekend dad to his young daughter. The only thing he takes comfort in is smoking marijuana and chess games with Ibou, his Senegalese roommate. When Ibou becomes ill, a municipal employee exacerbates the emergency situation, and Ben pours his energy into a lawsuit against the city. Meanwhile, Ibou's beautiful sister Khadi arrives from Senegal, and Ben's life begins to turn around.